Analisis Cemaran Makanan dengan Kandungan Methanyl Yellow di Kota Banyuwangi - Eka Zuristia Putri; Ririh Yudhastuti (Media Gizi Kesmas, 2023)
Background: Food is the most basic human need for survival. Food contamination can also be in the form of contamination originating from Food Additives (BTP) and the addition of hazardous substances that are misused in food. Supervision of hazardous materials abused in food. Based on the Joint Regulations of the Minister of Home Affairs of the Republic of Indonesia and the Head of BPOM RI Number 43 of 2013 and Number 2 of 2013 concerning Control of Hazardous Substances Misused in Food, one of which is carried out on types of hazardous materials with yellow methanyl dye (methanyl yellow). Objectives: The study was conducted to determine the content of methanyl yellow used in food circulating in traditional markets and supermarkets in the city of Banyuwangi by random sampling. Methods: The study was conducted using a qualitative test in which the researcher could identify the methanyl yellow dye contained in food ingredients by using a test by comparing the test color with the methanyl yellow color. Testing for food contamination was carried out in the SIKIA environmental health laboratory room, Airlangga University, Banyuwangi on Tuesday, 26 February 2019 at 11.00-14.40 with random sampling. Results : Testing for methanyl yellow content in food samples obtained results from 15 samples tested including yellow jelly at the Banyuwangi market, yellow crackers at the Blambangan market, soto seasoning at the Blambangan market, turmeric powder at the Blambangan market, yellow crackers at the Blambangan market, soto seasoning at Blambangan market, yellow noodles at Blambangan park, "Floridina” brand drink, "Marimas Jeruk brand powder”, wet yellow noodles near Blambangan park, gule seasoning near Blambangan park, instant seasoning "Fried chicken mix”, packaged jelly at the shop groceries, yellow crackers at the Cungking market, "Finto” brand powder drinks at the grocery store. Conclusions: The results of the sample testing obtained from 15 test samples explained that none of the samples experienced a change in color, or in another sense, all samples were free of methanyl yellow dye.